The Analysis of Collective Efficacy Perceptions of Athletes Playing in Table Tennis Leagues In Turkey in Terms of Some Variables, - Yücel, A. S., Korkmaz, M., Çoban, F. (My University, 2013)
In team sports, trust and the belief in being successful (collective efficacy) among the athletes of team sports can be effective on performance. In the meantime, analyses of the factors that can be an effective factor on perceptions of collective efficacy become more of an issue in terms of bringing a different perspective to the subject. Therefore, the purpose here is to research the level of collective efficacy of athletes playing in table tennis leagues in Turkey and the reasons affecting it. Target population of the study is composed of 597 players playing in table tennis leagues of Turkey; its sample constitutes randomly selected 224 table tennis players. A two-part questionnaire containing questions related to the demographic features and collective conscious levels was applied to the participants. The questionnaire used in the study was previously used in another study and its reliability was provided. Data of the questionnaire obtained from the participants were analyzed with PASW Statistic 18 package program. Following the reliability analysis, Cronbach’s Alpha coefficient was found as 0.90. As directed to the purpose of the study, Pearson correlation coefficient was used in analysis of data and Kruskal Wallis test was applied in comparisons with three or more groups. Moreover, Chi-Square test was used for independence research. Regression analyses were carried out with the purpose of determining to what extent the variables affect each other. In line with the researches conducted and data obtained, significant relations (<0.05) were found between the participants’ age, period of being registered athletics, duration of playing in the same team and their collective efficacy perceptions. The more these variables increase, the more the belief in the team and skills of team players increase in a positive way. In summary, it was concluded that the variables of age,sex, period of being registered athletics, duration of playing in the same team and total number of athletes are the factors that are effective on collective efficacy perception and it was found that 82% of the participants are of the opinion that their teams have the capacity to show good performance.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Collective efficacy Table tennis Collective conscious Performance